The evolution of green food poducts and retailers\' eco-strategizing and green competitiveness in the Danish and Brazilian grocery sector - Mazzero, Marcelo Fernando (2017)
Grounded in an evolutionary approach to environmental sustainability, this thesis adds an understanding of the dynamics of the greening of the economy, particularly highlighting the neglected demand side aspect of the greening of markets. Since the emergence of green food markets in the 1980s and 1990s, this study investigates the role of retail groups in the development of the green food market in Denmark and Brazil. Accordingly, it investigates the rate and the direction of the greening of this process in those markets as well as the convergence and the impact of retailers\' strategizing in the grocery sector. Using the dynamic capabilities framework, it examines why, how and when the strategizing, performance and competitiveness of grocery retail groups co-evolved with the development of the Danish and Brazilian green food markets. This thesis contributes innovatively to the literature on at least three more aspects. Firstly, it advances the existing literature in adding combined qualitative and quantitative longitudinal firm-level data, which is analysed over time through a proposed set of macro (market-level), meso (sectoral-level), and micro (firm-level) dimensions\' indicators of green market analysis. Secondly, it provides the perspectives of the interviewed retail groups and market support stakeholders operating in the Danish and Brazilian green food markets. Thirdly, it provides an estimate of the green food sales in the Brazilian retail sector. Even though this thesis concludes that major retail groups in Denmark and Brazil were not the pioneers in the green food market, their collaboration with specialized organic food producers and market support stakeholders were rather central in making the green food market a viable business case. These retail groups were key players in the evolution of the green food market as they have played a vital role in scaling up the Danish and Brazilian green food markets to higher turnover levels. Furthermore, these retailers sensed the market potential for the green foods in the 1980s and 1990s, and particularly in the 2000s and onwards, and through strategizing have been able to size and transform the green food market in Brazil and Denmark. These retailers\' strategizing and related capabilities building have been key to the innovative changes in their business models, which have become markedly greener in this period due to their role in the development of the Danish and Brazilian green food markets. Finally, as Denmark is at a higher level of green food turnover than Brazil, it suggests a more mature stage of its green economy.